SISTEM INFORMASI TIKET BIOSKOP PADA BUARAN TEATER DI JAKARTA TIMUR BERBASIS WEB - Saryoko, Andi (LPPM Universitas Nusa Mandiri, 2017)
Cinema Buaran Theatre is a company engaged in the field of tourism and entertainment. The problems faced by Cinema Buaran Theatre in business processes, namely in terms of booking a ticket using a manual system by using the ticket the ticket and thus require long lines and how marketing is also still manual so as to find out the schedule publishers film is still very poor in providing information and submission to the buyers. Based on these problems the author gives a solution to turn to web-based information systems. With the hope of reducing the errors that are common in the manual process to provide input in the use of computer systems to be more efficiency in the business process and can improve business processes.